ANALISIS PROFIL KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV SD NEGERI LOCERET II DALAM PEMBELAJARAN IPS - Siska Nur Wahida (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Critical thinking skills are crucial for the development of students' cognitive abilities and influence academic achievement, particularly in social studies, which requires reasoning and appropriate solutions. This study aims to describe the profile of fourth-grade students' critical thinking skills at Loceret II Elementary School in social studies. The study used a qualitative approach using observation, interviews, and documentation techniques. The results indicate that students have varying abilities in each critical thinking indicator. For the "ability to identify and understand problems" indicator, most students were able to grasp the core of the problem, although they had difficulty with more complex questions. For the "evaluating evidence and arguments" indicator, some students still struggled to distinguish between fact and opinion. The "making logical inferences" and "monitoring and reflecting on thought processes" abilities also showed progress but required further guidance. The conclusion of this study is that although students' critical thinking skills have begun to develop, a more structured and sustainable approach is still needed to improve their critical thinking abilities in social studies